A STUDY OF THE IMPACT OF SOCIAL MEDIA ON PERSONAL INVESTMENTS - Rajat Agrawal, Swati Mishra, Pratishtha Mathur and Sakshi Arora (South Eastern European Journal of Public Health, 2025)
The rise of social media has transformed the way individuals interact, access information, and make financial decisions. This study explores the impact of social media on personal investment choices, analyzing both the benefits and drawbacks of using social media as a financial information source. The research delves into how investor sentiment, risk perception, and decision-making are influenced by social media platforms. Findings suggest that while social media facilitates easy access to financial insights and market trends, it also poses risks such as misinformation, herd mentality, and emotionally driven investment behavior. The study underscores the need for investors to critically evaluate social media content and supplement it with traditional financial analysis to make informed investment decisions.